KOMUNIKASI ANTARBUDAYA MAHASISWA PESERTA PROGRAM INDONESIAN INTERNATIONAL STUDENT MOBILITY AWARDS (IISMA) DI RUSIA - Ari Budiarti; Hafied Cangara; Umaimah Wahid (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2022)
Indonesian students who take part in the Indonesian International Student Mobility Awards program in Russia may encounter challenges when interacting with local residents due to the relatively foreign culture, including language. This study was conducted to describe the facts that occurred in the process of intercultural communication during Indonesian students participating in the program in Russia. The method used in this research is a qualitative approach with case study research methods. The researcher chose to use a case study because the researcher wanted to conduct an in-depth search of programs, events and process activities for one or more individuals who were limited by time and activity. Furthermore, the researchers collected complete information using a variety of data collection procedures over a sufficient period of time. The results of this study indicate a tendency for the contribution of conceptual filters according to Gudykunst Kim's cultural communication model which includes, culture, socio-culture, psycho-culture, and environment that affect the interaction process of program participants while in Russia. Indonesian students participating in the Indonesian International Student Mobility Awards program who choose Russia as their destination country are advised in advance to take a basic level Russian language course in Indonesia.